Differential roles of type I topoisomerases in regulating HPV pathogenesis - Arushi Vats; Conor W. Templeton; Laimonis Laimins (Proceedings of the National Academy of Sciences, 2026)
High-risk human papillomaviruses (HPVs) activate the Ataxia Telangiectasia Mutated and Ataxia Telangiectasia and Rad3-Related pathways by inducing DNA breaks through the action of viral oncoproteins E6 and E7, which target factors such as topoisomerases. Type I topoisomerases cleave and religate a single strand of DNA, and little is known about how they regulate HPV pathogenesis. The levels of type I topoisomerases, TOP1α, TOP3α, and TOP3β, were all elevated in cells maintaining high-risk HPV genomes, as well as in squamous cell carcinomas. Only TOP1α and TOP3β, but not TOP3α, bound to HPV genomes and were critical for regulating viral gene transcription and replication with little effect on cell growth. Furthermore, the knockdown of TOP1α or TOP3β reduced levels of DNA breaks and differentially altered the expression of genes in key pathways. TOP1α knockdown reduced the expression of IL6 and activation of the procytokine signaling pathway. In contrast, TOP3β targeted EGR3, which regulates growth and differentiation. Finally, TOP1α and TOP3β differentially regulate the formation of R-loops, which are critical for viral replication. These findings demonstrate the differential roles of type I topoisomerases in HPV pathogenesis.